Factors Associated with Adherence to Blood Glucose Test among Diabetes Mellitus Patients at Prof. Dr. W. Z. Johannes Hospital, Kupang - Timuneno, Dessy Nelciani; Tira, Deviarbi Sakke; Manurung, Imelda F.E (Indonesian Journal of Medicine, 2016)
Background: Blood glucose level test for the Diabetes Mellitus patients is a procedure to monitor blood glucose level control and early detect complication of the disease. This study aimed to investigate the factors associated with adherence to blood glucose test among diabetes mellitus patientsat Prof. dr. W. Z. Johannes Hospital, Kupang.Subjects and Method: This was an analytic study withcross sectional study. A total of 93 Diabetes Mellitus patientswho had attended Internal Medicine Clinic at Prof. dr. W. Z. Johannes Hospital, Kupang, for at least 10 years, were sampled for this study. This sample consisted of 45 patients who adhered and 48 patients did not adhere to blood glucose test. Association of variables under study was analyze by chi square test.Results: There is a positive but weak relationship between adherence to blood glucose test and distance to health care facility (C=0.28; p=0.005), as well as family support(C=0.21; p=0.043).Conclusion: the health care authority should consider providing health care service for diabetes mellitus patients as close as possible to their home. In addition families of the patient are suggested to support their family members with diabetes mellitus in controlling blood glucose regularly.Keywords: adherence, blood â glucose level, diabetes mellitus.Correspondence:Â Dessy Nelciani Timuneno. Epidemiology and Biostatistics, School of Public Health, Nusa Cendana University, Kupang.Indonesian Journal of Medicine (2016), 1(1): 1-11https://doi.org/10.26911/theijmed.2016.01.01.02